Psychiatry morning report: beyond the Pearls - Duong, Tammy; Tamas, Rebecca L.; Ureste, Peter (Amsterdam Elsevier, 2021)
Psychiatry Morning Report: Beyond the Pearls is a case-based reference that covers the key material included on the USMLE Step 2 and Step 3, as well as the psychiatry clerkship. Focusing on the practical information you need to know, it teaches how to analyze a clinical vignette in the style of a morning report conference, sharpening your clinical decision-making skills and helping you formulate an evidence-based approach to realistic patient scenarios--back cover.
Includes bibliographical references and index.
Keywords: Psychiatry; Psychiatry -- Case studies; Mental illness -- Treatment; Clinical psychology; Psychiatry; Mental Disorders -- therapy; Psychology, Clinical; Maladies mentales -- Traitement; Psychologie clinique; Psychiatry; Case Reports; Case studies